Volar yo quiero - Barron, Judy.; Moore, Cyd. (New York, NY Scholastic, 1995)
A young girl imagines all the places she would go if she could fly.
Translation of: I want to learn to fly.
Keywords: Imagination -- Juvenile fiction; Flight -- Juvenile fiction; Spanish language materials -- Juvenile fiction; Fiction